A Review of Indentation Theory. (2018) - Arunkumar, S.
Abstract: Indentation hardness testing has been used for many years to assess the quality of materials. Recently, with the advent of computers and sophisticated instruments, the hardness test and result analysis has been automated. Thus, it has become a ubiquitous tool among scientific and engineering community and in industry as well. Consequently, now it is possible to extract the more fundamental properties like young's modulus, yield stress, creep, fatigue and fracture properties using the correlations developed between indentation and conventional full-scale test results. This paper reviews the evolution of different hardness testing methods and mechanisms of indentation. The information provided the mechanisms of indentation like nature and extent of deformation zone beneath the indenter provides a basis for setting the limits on the variables on hardness testing practice. In addition the influence of indentation parameters like strain hardening exponent, friction, residual stress etc. on the nature of deformation of the specimen is explained